Unusual late-fall wildfire in a pre-Alpine Fagus sylvatica forest reduced fine roots in the shallower soil layer and shifted very fine-root growth to deeper soil depth - Antonio Montagnoli; Mattia Terzaghi; Alessio Miali; Donato Chiatante; R. Kasten Dumroese (Scientific Reports, 2023)
Abstract After an unusual, late-fall wildfire in a European beech (Fagus sylvatica L.) forest in the pre-Alps of northern Italy, the finest roots (0‒0.3 mm diameter) were generally the most responsive to fire, with the effect more pronounced at the shallowest soil depth. While roots 0.3‒1 mm in diameter had their length and biomass at the shallowest soil depth reduced by fire, fire stimulated more length and biomass at the deepest soil depth compared to the control. Fire elevated the total length of dead roots and their biomass immediately and this result persisted through the first spring, after which control and fire-impacted trees had similar fine root turnover. Our results unveiled the fine-root response to fire when subdivided by diameter size and soil depth, adding to the paucity of data concerning fire impacts on beech roots in a natural condition and providing the basis for understanding unusual fire occurrence on root traits. This study suggests that F. sylvatica trees can adapt to wildfire by plastically changing the distribution of fine-root growth, indicating a resilience mechanism to disturbance.